Differentiated tonsil-derived mesenchymal stem cells embedded in Matrigel restore parathyroid cell functions in rats with parathyroidectomy. (October 2015) - Park, Yoon Shin; Kim, Han Su; Jin, Yoon Mi; Yu, Yeonsil; Kim, Ha Yeong; Park, Hae Sang; Jung, Sung-Chul; Han, Ki-Hwan; Park, Yoon Jeong; Ryu, Kyung-Ha; Jo, Inho
Abstract: Parathyroid cells release parathyroid hormone (PTH), which controls calcium homeostasis. Loss of parathyroid cells results in hypoparathyroidism and consequent low-turnover bone disease. Here, we investigated whether our recently-established human tonsil-derived mesenchymal stem cells (TMSC) restore in vivo parathyroid cell function in rats with parathyroidectomy (PTX). Compared with undifferentiated control TMSC, TMSC differentiated with activin A and soluble sonic hedgehog induced a significant release of PTH as early as day 7, with increased PTH release occurring in response to lower calcium levels and vice versa . Released PTH increased osteocalcin expression and alizarin red S staining in preosteoblastic cells, indicating its functional activity. PTX rats fed calcium-free diet only survived for ∼10 days. Subcutaneous injection with TMSC alone did not increase their survival rates, regardless of differentiation. However, survival rates increased for up to 28 days in response to TMSC embedded in Matrigel (TMSC-MA), showing 40% and 80% in control and differentiated TMSC-MA, respectively. When compared with continuous increases by control TMSC-MA, stable levels of secreted PTH and serum ionized calcium were found in PTX rats with differentiated TMSC-MA. This is the first report that differentiated TMSC resemble parathyroid cells and, if embedded in Matrigel, restore in vivo parathyroid function.